A microporous europium–organic framework anchored with open –COOH groups for selective cation sensing. Issue 41 (30th September 2016) - Qian, Jinjie; Yu, Panpan; Huang, Shaoming
Abstract : [Eu2 (BPTC)(H2 BPTC)(DMF)4 ]·Guest (BMM- 7 ) is a new 3-dimensional microporous metal–organic framework based on a functional [Eu2 (COO)6 (DMF)2 ] secondary building unit, which is rendered with uncoordinated carboxylate groups protruding into the channels. Abstract : [Eu2 (BPTC)(H2 BPTC)(DMF)4 ]·Guest (BMM- 7 ) is a new 3-dimensional microporous metal–organic framework based on a functional [Eu2 (COO)6 (DMF)2 ] secondary building unit, which is rendered with uncoordinated carboxylate groups protruding into the channels. The microporous nature is confirmed using nitrogen isotherms at 77 Kelvin and the open –COOH groups can effectively and selectively capture Cu(ii) cations in the exchange process.